ISSUES OF DEVELOPMENT OF THE TEXTILE AND SEWINGKNITTING INDUSTRY ENTERPRISES’ QUALITY MANAGEMENT SYSTEMS AND IMPROVEMENT OF METHODS FOR ITS EVALUATION (World Bulletin of Management and Law, 2024)
The article substantiates the importance of developing a quality management system for textile and sewing-knitting industry enterprises in the digital economy, improves methods for its assessment, and, based on the analysis, develops a strategy and model for the development of a quality management system.